Aesthetics and film - Thomson-Jones, Katherine (Continuum, 2008)
This is a philosophical study of form of moving image media - what film can do for philosophy, and philosophy for film.
Includes bibliographical references and index
Keywords: Film; Ästhetik; Motion pictures -- Aesthetics; Filmästhetik